Africa in Soviet studies : annual 1983 - USSR Academy of Sciences- Africa Institute (Moscow : "Nauka" Pub. House, Central Dept. of Oriental Literature, 1983)
This current issue of the Annual by Africa Institute, USSR Academy of Sciences, contains reports on Soviet foreign policy and Soviet-African cooperation. A number of articles examine some aspects of economic, social and cultural development of African countries. The Annual includes data on scientific activities, reviews of both Soviet and foreign works on Africa and personalia.
Includes index.
Includes bibliographical references: p. 334-372.
ne 23/07/2019
Ref
Keywords: African studies; USSR; Area studies; Study skills; Africa; Soviet Union